Agricultural growth and investment options for poverty reduction in Rwanda - Diao, Xinshen; Fan, Shenggen; Yu, Bingxin; Kanyarukiga, Sam (International Food Policy Research Institute, 2007)
An economywide, multimarket (EMM) model was developed for Rwanda to analyze the linkages and trade-offs between growth and poverty reduction goals at both macro- and micro-economic levels. The model includes 30 agricultural commodities or commodity groups from eight broad agricultural subsectors, along with two aggregated nonagricultural sectors. The analysis compares the economic, income, and poverty effects of a variety of growth scenarios based on existing national subsector growth targets. The analysis shows 6 percent of CAADP’s agricultural GDP growth target is achievable if growth reaches its target at the agricultural subsectoral level. But it is not enough for the country to achieve the MDG One, although the national poverty rate in 2015 will be 17 percent lower than that in 2005. Moreover, the household groups with the smallest landholding size, female-headed, or with few opportunities to participate cash crop production seem to benefit less from such growth. The study also examines the different growth-poverty linkages at agricultural subsector level, and shows that growth driven by productivity increases in staple crops and livestock production can reduce the poverty more than in the case where growth is driven by export crops or by the nonagricultural sector. The analysis also shows that to achieve growth required by CAADP and MDG One, the country needs to substantially beef up its public investment in agriculture. The share of agricultural spending in total government spending is required to increase from the current level of 5 percent to 10-35 percent in 2015.